2021
DOI: 10.15562/jdmfs.v6i3.989
|View full text |Cite
|
Sign up to set email alerts
|

Role of secretome mesenchymal stem cells as immunomodulator in periodontal diseases

Abstract: Objective: The purpose of this review literature is to look at the mechanism of mesenchymal stem cell secretome in the regeneration of periodontal tissue. Methods: This literature review was collected from several journals and research that has been done, where the application of Mesenchymal stem cells (MSCs) promises a favourable result for cellbased therapy in inflammatory diseases, immune system disorders, regeneration, and tissue repair. Results: MSCs possess a potent immunomodulatory function, paracrine e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Furthermore, the presence of growth factors in the DPMSCS can accelerate wound healing by inducing inflammatory mediators such as interleukin-1 (IL-1), Interleukin-6 (IL-6), and prostaglandin E2 (PGE2) in vitro, reducing the initial inflammatory reaction in vivo [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the presence of growth factors in the DPMSCS can accelerate wound healing by inducing inflammatory mediators such as interleukin-1 (IL-1), Interleukin-6 (IL-6), and prostaglandin E2 (PGE2) in vitro, reducing the initial inflammatory reaction in vivo [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…the induction of T cells and macrophages. The paracrine effects of MSCs are critical for maintaining epithelial cell integrity and promoting angiogenesis through their ability to regulate cell proliferation and differentiation [25,[36][37][38]. This study's results were only limited to traumatic ulcer animal model using Wistar rats (R. novergicus).…”
Section: Discussionmentioning
confidence: 99%
“…6 Studies have shown the immunomodulatory effect of MSCs. 7 However, there is a lack of information regarding the effect of secretomes derived from human umbilical cord MSCs (UCMSCs) in vivo. Therefore, this study aimed to investigate the immunomodulatory activity of secretomes.…”
Section: Introductionmentioning
confidence: 99%